Effects of Light Quality and Intensity on Diurnal Patterns and Rates of Photo-Assimilate Translocation and Transpiration in Tomato Leaves - Lanoue, Jason; Leonardos, Evangelos D.; Grodzinski, Bernard (Frontiers in Plant Science, 2018)
Translocation of assimilates is a fundamental process involving carbon and water balance affecting source/sink relationships. Diurnal patterns of CO2 exchange, translocation (carbon export), and transpiration of an intact tomato source leaf were determined during 14CO2 steady-state labelling under different wavelengths at three pre-set photosynthetic rates. Daily patterns showed that photosynthesis and export were supported by all wavelengths of light tested including orange and green. Export in the light, under all wavelengths was always higher than that at night. Export in the light varied from 65-83% of the total daily carbon fixed, depending on light intensity. Photosynthesis and export were highly correlated under all wavelengths (r=0.90-0.96). Export as a percentage of photosynthesis (relative export) decreased as photosynthesis increased by increasing light intensity under all wavelengths. These data indicate an upper limit for export under all spectral conditions. Interestingly, only at the medium photosynthetic rate, relative export under the blue and the orange light-emitting diodes (LEDs) were higher than under white and red-white LEDs. Stomatal conductance, transpiration rates, and water-use-efficiency showed similar daily patterns under all wavelengths. Illuminating tomato leaves with different spectral quality resulted in similar carbon export rates, but stomatal conductance and transpiration rates varied due to wavelength specific control of stomatal function. Thus, we caution that the link between transpiration and C-export may be more complex than previously thought. In summary, these data indicate that orange and green LEDs, not simply the traditionally used red and blue LEDs, should be considered and tested when designing lighting systems for optimizing source leaf strength during plant production in controlled environment systems. In addition, knowledge related to the interplay between water and C-movement within a plant and how they are affected by environmental stimuli, is needed to develop a better understanding of source/sink relationships.